2013
DOI: 10.1136/gutjnl-2012-304058
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid ethyl ester synthase inhibition ameliorates ethanol-induced Ca2+-dependent mitochondrial dysfunction and acute pancreatitis

Abstract: ObjectiveNon-oxidative metabolism of ethanol (NOME) produces fatty acid ethyl esters (FAEEs) via carboxylester lipase (CEL) and other enzyme action implicated in mitochondrial injury and acute pancreatitis (AP). This study investigated the relative importance of oxidative and non-oxidative pathways in mitochondrial dysfunction, pancreatic damage and development of alcoholic AP, and whether deleterious effects of NOME are preventable.DesignIntracellular calcium ([Ca2+]C), NAD(P)H, mitochondrial membrane potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
186
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(195 citation statements)
references
References 47 publications
3
186
1
5
Order By: Relevance
“…22 These recent findings published by Criddle et al 22 partly differ from our current work and their earlier studies. 17,21 In our current work, similar to their 2006 study, we note FAEEs to be less toxic than the parent FAs.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…22 These recent findings published by Criddle et al 22 partly differ from our current work and their earlier studies. 17,21 In our current work, similar to their 2006 study, we note FAEEs to be less toxic than the parent FAs.…”
Section: Discussioncontrasting
confidence: 86%
“…In addition, in contrast to their 2006 study which showed FAEE cytotoxicity depends on their conversion to FAs 21 ; their 2014 study 22 showed this to depend on the conversion of POA to POAEE. This increase in cytosolic calcium and severity of pancreatitis were significantly reduced with the agent 3-benzyl-6-chloro-2-pyrone (3-BCP), a generic serine protease inhibitor, 68,69 which they proposed Figure 5 Triolein administration causes a worse cytokine response and inflammation compared with OAEE.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…smoking, diet) must also be responsible for the induction of the disease. Furthermore, the importance of nonoxidative ethanol metabolites such as fatty acid ethyl esters as well as cytotoxic fatty acids in acute pancreatitis is now being increasingly recognized [52].…”
Section: Effects Of Pancreatitis Inducing Factors On Cftrmentioning
confidence: 99%